A Proposed Model for Strategic Planning in Technology and Vocational Education - *, Suharno; *, Ranto; Prawiro, Bambang; Sudibyo, C. (Sebelas Maret University, 2016)
This paper describes the methods of strategic planning for Technology and Vocational Education (TVE).For this purpose, the SWOT method has been used, integrated with the Balanced Score Card. The steps taken in this study were: first, conducting a SWOT analysis qualitatively; second, doing a SWOT research quantitatively; and third, using the Balanced Score Card to formulate the strategic issues and determine the effective strategy for organization. The object of this study was the Mechanical Engineering Education (MEE) Study Program and Civil Engineering Education (CEE) Study Program in Faculty of Teacher Training and Educational of Sebelas Maret University of Indonesia. The subjects of this study were the planning team, heads of the study programs, and their students. The result shows that SWOT method integrated with the Balanced Score Card can be used effectively to find out the exact strategic issues. Based on these strategic issues, the planning team can easily formulate the strategic planning in each study program.